PENGARUH INDEKS KEPUASAN MASYARAKAT (IKM) TERHADAP PELAYANAN PUBLIK PADA KANTOR CAMAT INDRAJAYA - Zulfikar, Zulfikar; Zulkifli, Zulkifli; Jayus, Zuliaden; Awaluddin, Awaluddin (Universitas Bina Taruna Gorontalo, 2025)
This research was conducted at the Indrajaya District Office, Pidie Regency, which was the object of the research on the public satisfaction index (IKM) towards public services. This research used a quantitative method while the writing used a descriptive method with data collection techniques through questionnaires and observations of the implementation of public services carried out by Government Agencies, namely the Indrajaya District Office. The results of the questionnaire data testing and data processing were in accordance with the general guidelines of the Decree of the Minister of Empowerment of State Civil Apparatus (KEPMEN-PAN Number: KEP / 25 / M.PAN / 2/2004), data processing obtained results that the Public Satisfaction Index (IKM) showed good results with a score of 74.00 in the good category. While to measure the influence of the Public Satisfaction Index (IKM) variable on Public Services at the Indrajaya District Office, Pidie Regency is at 71.4 percent, in other words the Public Satisfaction Index (IKM) has an effect on Public Services at the Indrajaya District Office, Pidie Regency. The research conducted by the author can provide a contribution to public service agencies in this case the Indrajaya District Office, Pidie Regency.